Kidney donor profile index and post‐transplant health care utilization: Implications for value of transplant care delivery. Issue 6 (20th May 2022) - Mour, Girish K.; Chang, Yu‐Hui; Calderon, Esteban; Chang, James M.; Velazco, Cristine S.; Jadlowiec, Caroline C.; Reddy, Kunam S.; Heilman, Raymond L.; Mathur, Amit K.
Abstract: Background: Centers discard high kidney donor profile index (KDPI) allografts, potentially related to delayed graft function and prolonged hospital use by kidney transplant recipients (KTR). We sought to determine whether high KDPI KTRs have excess health care utilization. Methods: We conducted a retrospective cohort study from a high‐volume center analyzing KTRs from January 3, 2011 to April 12, 2015 ( n = 652). We measured differences in hospital use, emergency visits, and outpatient visits within the first 90 days between low (≤85%) versus high KDPI (>85%) KTRs, as well as long‐term graft function and patient survival. Results: High ( n = 107) and low KDPI ( n = 545) KTRs had similar length of stay (median = 3 days, P = .66), and readmission rates at 7, 30, and 90 days after surgery (all, P > .05). High KDPI kidneys were not associated with excess utilization of the hospital, emergency services, outpatient transplant clinics, or ambulatory infusion visits on univariate or multivariate analysis (all, P > .05). Low KDPI KTRs had significantly better eGFR at 2 years (Low vs. High KDPI: 60.35 vs. 41.54 ml/min, P < .001), but similar 3‐year patient and graft survival (both, P > .09). Conclusions: High and low KDPI KTRs demonstrated similar 90‐day risk‐adjusted health care utilization, which should encourage use of high KDPI kidneys.